Effects of dietary combination of chromium and biotin on growth performance, meat quality and oxidative stress markers in heat distressed Japanese quail - Kazim, S; Onderci, M; Sahin, N; Cikim, G; Juturu, V; Kucuk, O (Federation Amer Soc Exp Biol, 2004)
[Abstract Not Available]
Experimental Biology 2004 Meeting -- APR 17-21, 2004 -- Washington, DC